1995
DOI: 10.1016/0006-3207(94)00102-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of road traffic on amphibian density

Abstract: We studied the effect of traffic intensity on local abundance of anurans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
344
6
15

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(387 citation statements)
references
References 13 publications
22
344
6
15
Order By: Relevance
“…The association between genetic and geographical distances within Brighton was investigated further by examination of urban boundary development in the town over time from OS maps. The number of major roads and railways intersecting the intersite transects was also determined, as roads are known to be significant barriers to migrating amphibians (Cooke, 1972;Fahrig et al, 1995). Weighting the distance in kilometres by 1 x the proportion of the transect developed post-1932 improved correlation with the Cavalli-Sforza chord genetic distance slightly, to r = 0.58, P (Mantel) = 0.004 with town parks and r = 0.74, P (Mantel) = 0.001 without them.…”
Section: Genetic Analysismentioning
confidence: 99%
“…The association between genetic and geographical distances within Brighton was investigated further by examination of urban boundary development in the town over time from OS maps. The number of major roads and railways intersecting the intersite transects was also determined, as roads are known to be significant barriers to migrating amphibians (Cooke, 1972;Fahrig et al, 1995). Weighting the distance in kilometres by 1 x the proportion of the transect developed post-1932 improved correlation with the Cavalli-Sforza chord genetic distance slightly, to r = 0.58, P (Mantel) = 0.004 with town parks and r = 0.74, P (Mantel) = 0.001 without them.…”
Section: Genetic Analysismentioning
confidence: 99%
“…Among the negative road impacts are situations of altered animal behaviour due to roads (reviewed in Trombulak and Frissell 2000), landscape impermeability to small (Richardson et al 1997;Gerlach and Musolf 2000) and larger mammals (Hansen 1983;Thiel 1985;McLellan and Shackleton 1988;Romin and Bissonette 1996) and increased amphibian mortality (Fahrig et al 1995;Carr andFahrig 2001, Cushman 2006). Physical and chemical conditions in areas subjected to road construction are altered (Trombulak and Frissell 2000) as are the hydrologic and geomorphologic attributes of a site (Jones et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Merriam et al 1989;Vos and Chardon 1998), increased mortality (Rosen and Lowe 1994;Fahrig et al 1995;Barthelmess and Brooks 2010), habitat fragmentation and edge effects (Mader 1984;Andrews 1990;Soulé et al 1992;Thiollay 1993' Henjum et al 1994Wigley and Roberts 1994;Jaeger et al 2007;Roedenbeck et al 2007;Spellerberg 1998), invasion by exotic species (Lonsdale and Lane 1994), or increased human access to wildlife habitats (Graham et al 2010), all of which are expected to increase local extinction rates or decrease local recolonization rates.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of roads and traffic intensity can result in the direct mortality of amphibian species [149,150]. For instance, a study in Canada found that with increasing traffic intensity, the proportion of dead frogs and toads increased while the density decreased [149].…”
Section: Roadsmentioning
confidence: 99%
“…For instance, a study in Canada found that with increasing traffic intensity, the proportion of dead frogs and toads increased while the density decreased [149]. Another study, which recorded the deaths of newt and frog species during attempted road crossings, determined that velocity of the species and diurnal movement pattern of both species and vehicles influenced likelihood of road mortality [151].…”
Section: Roadsmentioning
confidence: 99%